2022
DOI: 10.1101/2022.08.31.506114
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Associations between thinner retinal neuronal layers and suboptimal brain structural integrity: Are the eyes a window to the brain?

Abstract: We investigated the extent to which measures of retinal neuronal thickness capture variability in the structural integrity of the brain in a large population-based cohort followed from birth to midlife. Using data from the Dunedin Multidisciplinary Health and Development Study (n=1037; analytic n=828, aged 45 years), we specifically tested for associations between optical coherence tomography-measured retinal neuronal layers and MRI-measured structural brain integrity. We found that Study members who had thinn… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…Extending our prior analysis based on data from 2131 UK Biobank participants [12], the current results concur with the previously observed association between hippocampal volume and inner retinal thickness, now supported by a larger sample (n = 6446). This aligns with findings from the Rotterdam study, the Rhineland study, and others [36,40,[61][62][63][64]. Hippocampal atrophy is one of the hallmark features of overt AD and mild cognitive impairment, and is a risk factor for future AD in cognitively intact elderly people [65][66][67].…”
Section: Discussionsupporting
confidence: 87%
“…Extending our prior analysis based on data from 2131 UK Biobank participants [12], the current results concur with the previously observed association between hippocampal volume and inner retinal thickness, now supported by a larger sample (n = 6446). This aligns with findings from the Rotterdam study, the Rhineland study, and others [36,40,[61][62][63][64]. Hippocampal atrophy is one of the hallmark features of overt AD and mild cognitive impairment, and is a risk factor for future AD in cognitively intact elderly people [65][66][67].…”
Section: Discussionsupporting
confidence: 87%
“…The retina is embryonically formed as part of the diencephalon, which later becomes the thalamus, thus being developmentally related to specific brain regions. Consequently, the retina has been considered a unique window into altered brain structure/function 1,3 and brain disorders 4 , such as Alzheimer's disease [5][6][7][8] , Parkinson's disease 9 , stroke 10,11 , cerebral small vessel disease 12 , schizophrenia 13 , cognitive decline 11,14,15 , and many others. For example, it has been extensively studied that retinal neurodegeneration can be used as an easily accessible biomarker to identify individuals at high risk of developing Alzheimer's disease or those with preclinical Alzheimer's disease 6,8,[16][17][18] .…”
mentioning
confidence: 99%
“…Consequently, the retina has been considered a unique window into altered brain structure/function 1,3 and brain disorders 4 , such as Alzheimer's disease [5][6][7][8] , Parkinson's disease 9 , stroke 10,11 , cerebral small vessel disease 12 , schizophrenia 13 , cognitive decline 11,14,15 , and many others. For example, it has been extensively studied that retinal neurodegeneration can be used as an easily accessible biomarker to identify individuals at high risk of developing Alzheimer's disease or those with preclinical Alzheimer's disease 6,8,[16][17][18] . Retinal abnormalities have also been frequently reported in Parkinson's disease, and animal models have demonstrated that similar molecular mechanisms underlie Parkinson's disease pathology and neurodegeneration in parkinsonian eyes 9 .…”
mentioning
confidence: 99%